Community-based interventions to prevent fatal overdose from illegal drugs: a systematic review protocol. Issue 11 (3rd November 2015) - Okolie, Chukwudi; Evans, Bridie Angela; John, Ann; Moore, Chris; Russell, Daphne; Snooks, Helen
Abstract : Introduction: Drug overdose is the most frequent cause of death among people who misuse illegal drugs. People who inject these drugs are 14–17 times more likely to die than their non-drug using peers. Various strategies to reduce drug-related deaths have failed to meet target reductions. Research into community-based interventions for preventing drug overdose deaths is promising. This review seeks to identify published studies describing community-based interventions and to evaluate their effectiveness at reducing drug overdose deaths. Methods and analysis: We will systematically search key electronic databases using a search strategy which groups terms into four facets: (1) Overdose event, (2) Drug classification, (3) Intervention and (4) Setting. Searches will be limited where possible to international literature published in English between 1998 and 2014. Data will be extracted by two independent reviewers using a predefined table adapted from the Cochrane Collaboration handbook. The quality of included studies will be evaluated using the Cochrane Collaboration's tool for assessing risk of bias. We will conduct a meta-analysis for variables which can be compared across studies, using statistical methods to control for heterogeneity where appropriate. Where clinical or statistical heterogeneity prevents a valid numerical synthesis, we will employ a narrative synthesis to describe community-based interventions, their delivery and use and how effectively they prevent fatal overdoses. Ethics and dissemination: We will publish findings from this systematic review in a peer-reviewed scientific journal and present results at national and international conferences. It will be disseminated electronically and in print. Trial registration number: PROSPERO CRD42015017833.